Comparative analysis of different DNA extraction methods and their genotyping efficiency in Mexican population - Ríos-Sánchez, Efraín; Calleros, Esperanza; González-Zamora, Alberto; Rubio, Julieta; Martínez, Ollin C.; Martínez, Aurora; Hernández, Sandra; Pérez-Morales, Rebeca (Acta Universitaria, 2016)
Genetic variability studies have presented inconsistencies between populations, mainly because methods of deoxyribonucleic acid (DNA) extraction and genotyping techniques show high variability between them, leading to an erroneous assignment of genotypes. The objective of this study is compare different techniques for DNA extraction and genotyping of polymorphisms. To perform this study, DNA from 10 blood samples corresponding to mestizo Mexicans was analyzed and purified by methods of phenol-chloroform-isoamyl alcohol (PCA), salting out gradient (SG), sucrose gradient (SCG), DNAzol ® method and DNeasy Blood & Tissue Kit ®. GSTT1*0 and GSTM1*0 polymorphisms were genotyped by multiplex PCR, CYP1A1*2C by PCR-RFLP’s assay and AhR Arg554Lys by real-time PCR. Results shown that amount, purity and integrity of DNA were evaluated. Different methods results showed significant differences (p < 0.001). Molecular analyses showed that PCA method presents inhibitors for PCR reaction because it was not possible to amplify fragments in multiplex PCR and endpoint. Although, there was amplification in real time PCR. SG and SCG methods amplified all samples in three types of PCR and the results were concordant between them. While in PCR - RFLP analysis, samples extracted by DNAzol ® and DNeasy ® amplified only 80% of samples with no concordant results (50% for DNAzol ® and 80% for DNeasy ®). SG extraction methods and SCG showed higher DNA recovery, with optimal quality parameters for molecular analyses by PCR.